Consumer purchase behavior in livestream E-commerce platforms: An integrated technology acceptance and trust perspective - Lam, Nguyen Que (Edelweiss Applied Science and Technology, 2026)
This study examines the key factors and underlying mechanisms influencing consumer purchasing behavior in livestream shopping within Vietnam’s rapidly expanding e-commerce market. Despite the growing popularity of livestream commerce, empirical research explaining how technological, social, and trust-related factors jointly shape consumer behavior in emerging digital economies remains limited. To address this gap, the study proposes an integrated research model grounded in the Theory of Reasoned Action (TRA), the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM), and trust-based e-commerce frameworks. Data were collected from 463 Vietnamese consumers with a livestream shopping experience and analyzed using Cronbach’s Alpha, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM). The results show that perceived usefulness, perceived ease of use, streamer reputation, online consumer reviews, and trust positively influence purchase intention. Purchase intention, in turn, strongly predicts actual purchasing behavior and mediates the relationships between cognitive factors, attitudes, and behavior. The study concludes that effective livestream shopping strategies require not only technological usability but also trust-building and social influence mechanisms embedded in livestream interactions. This research extends consumer behavior theory to the livestream commerce context and offers practical implications for developing effective and sustainable livestream sales strategies in emerging markets.